2021
DOI: 10.1158/0008-5472.can-20-1992
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Receptor Tyrosine Kinases Mediates Acquired Resistance to MEK Inhibition in Malignant Peripheral Nerve Sheath Tumors

Abstract: Malignant peripheral nerve sheath tumors often arise in patients with neurofibromatosis type 1 and are among the most treatmentrefractory types of sarcoma. Overall survival in patients with relapsed disease remains poor, and thus novel therapeutic approaches are needed. NF1 is essential for negative regulation of RAS activity and is altered in about 90% of malignant peripheral nerve sheath tumors (MPNST). A complex interplay of upstream signaling and parallel RAS-driven pathways characterizes NF1driven tumorig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…A similar variation tendency in cyclin D1 expression was observed. As demonstrated in previous studies, MEK inhibition could reactivate MAPK signaling or upregulate parallel signaling pathways, particularly, the PI3K pathway, resulting in reduced efficacy of MEK inhibitors ( 27 ). It was also observed in S462 cells that compensatory increases in p-MEK and p-AKT occurred after 24 h of MEK inhibitor treatment.…”
Section: Resultsmentioning
confidence: 76%
“…A similar variation tendency in cyclin D1 expression was observed. As demonstrated in previous studies, MEK inhibition could reactivate MAPK signaling or upregulate parallel signaling pathways, particularly, the PI3K pathway, resulting in reduced efficacy of MEK inhibitors ( 27 ). It was also observed in S462 cells that compensatory increases in p-MEK and p-AKT occurred after 24 h of MEK inhibitor treatment.…”
Section: Resultsmentioning
confidence: 76%
“…Although the landmark trials only include inoperable patients, anecdotal reports suggest that MEK inhibitors could have a role. 59 However, although most of the patients do respond, tumor shrinkage is modest (15%-30%). Combination strategies might overcome resistance to monotherapy 56 , 57 and offer additional volumetric tumor shrinkage to further optimize surgery, but this is still an underexplored field of research in NF1-related PNs.…”
Section: Discussionmentioning
confidence: 99%
“…SHP2 inhibition enhances the efficacy of tyrosine kinase inhibitors (TKI), such as ALK/EGFR/FGFR inhibitors, in drug-resistant NSCLC and metastatic breast cancer, in which distinct RTK activation mediates adaptive and acquired resistance [25][26][27][28]. In addition, SHP2 inhibition (or depletion) also restores sensitivity to ERK signaling inhibition and has additive/synergistic anti-tumor effects when combined with KRAS G12C /RAF/MEK inhibitors in multiple models of cancers driven by hyperactivated RAS, including KRASmutant pancreatic, lung and colorectal cancers, KRAS WTamplified gastroesophageal cancer, RAS WT triple negative breast cancer (TNBC) and ovarian cancers, NRAS-mutant neuroblastoma, NF1-deficient MPNST, and BRAF-mutant colon and thyroid cancers, among others, through blocking signal transduction from most RTK that are reactivated through loss of negative feedback following ERK pathway inhibition [19,24,26,[29][30][31][32][33][34][35][36][37][38].…”
Section: The Role Of Shp2 In Dysregulated Rtk/ Ras/erk Signaling In Cmentioning
confidence: 99%
“…MEKi alone, however, has limited anti-tumor activity, leading to the notion that combinations that target the adaptively upregulated molecules that emerge upon loss of ERK-induced negative feedback should be effective. Our data suggested that a number of tyrosine and serine/threonine kinases become adaptively upregulated in response to MEKi, leading to challenges in the design of MEKi plus TKI combination strategies, as genomic or other predictive biomarkers to identify the adaptively changed RTK are not readily discernible [24,32]. In order to overcome this challenge, we posited that inhibition of the central node of convergence between the RTK and RAS recruitment to the membrane and activation -SHP2 -would serve as a viable strategy.…”
Section: The Combination Partner Shp2 As a Promising Co-target In Mpnmentioning
confidence: 99%